Development and Validation of an Analytical Method to Quantitate Tris(chloroisopropyl)phosphate in Rat and Mouse Plasma using Gas Chromatography with Flame Photometric Detection. Issue 1 (27th July 2018) - Collins, B J; Slade, D; Ryan, K; Mathias, R; Shan, A; Algaier, J; Aillon, K; Waidyanatha, S
Abstract: Tris(chloropropyl)phosphate (TCPP) is an organophosphorus flame retardant (OPFR) and plasticizer increasingly used in consumer products and as a replacement for brominated flame retardants. Commercially available TCPP is a mixture of four structural isomers the most abundant of which is tris(1-chloro-2-propyl)phosphate (TCPP-1). Although there is a widespread use of TCPP and potential for human exposure, there is limited data on the safety or toxicity of TCPP. The National Toxicology Program is conducting long-term studies to examine the toxicity of the TCPP in rats after lifetime exposure, including perinatal oral exposure. Quantitative estimates of internal dose are essential to interpret toxicological findings in rodents. To aid in this, a method was fully validated to quantitate the most abundant isomer, TCPP-1, in female Harlan Sprague Dawley (HSD) rat and B6C3F1 mouse plasma with partial validation in male rat plasma, and male and female mouse plasma. The method used protein precipitation using trichloroacetic acid followed by the extraction with toluene, and analysis by gas chromatography with flame photometric detection. The performance of the method was evaluated over 5–70 ng TCPP-1/mL plasma. The method was linear ( r ≥ 0.99), accurate (inter-day relative error: ≤ ± –7.2) and precise (inter-batch relative standard deviation: ≤27.5%). The validated method has lower limits of quantitation and detection of 5 and 0.9 ng/mL, respectively, in female HSD rat plasma and can be used on samples as small as 50 μL demonstrating the applicability to plasma samples from toxicology studies.